Finding Meaning in Life: Challenges Confronting Young People in Selected Novels by John McGahern - Asad Al-Ghalith; Mohsen Hashem (European Scientific Journal, ESJ, 2016)
This article aims at exploring the challenges that face the central characters in selected novels by the Irish writer John McGahern. The major characters in John McGahern's fiction are confronted by serious challenges and obstacles. This can be noted in many novels by McGahern such as The Dark and The Leave-taking . For instance, In The Dark, young Mahoney is dominated by his father who hinders his son's growth as a young man. Likewise, The Leave-taking is a book of challenges facing the youth. We are here told that Moran is a teacher who is about to lose his favorite job as a teacher simply because he ignores the church rituals and decides to marry a foreign divorcee in a registry office. Remarkably, each of these young people is confronted with a difficulty that hampers his present life and impedes his future aspirations. However, McGahern tells us that his characters struggle continuously to achieve some sort of settlement. Each one tries to set a plan for living that helps him to lead a happy life despite the heavy burden of challenges that he faces. By the end of each novel, we are astonished to see that each of the characters has admirably affirmed some meaning in his life. There is a universal lesson to be learned by youth everywhere from the examples offered by our author in these novels.